Wednesday

July 23, 2014

July 23, 2014

Posted by **mathstudent** on Saturday, June 9, 2007 at 11:56pm.

T1(c0 + c1*x) = 2c0 - 3c1*x

Using the standard bases, B = {1, x} and B' = {1, x, x^2}, what is the transformation matrix

[T1]B',B

T(c0 + c1*x) = 2c0 - 3c1*x --->

T(1) = 2

T(x) = -3x

So, the matrix elements are:

T_{1,1} = 2

T_{1,2} = 0

T_{2,1} = 0

T_{2,2} = -3

T_{3,1} = 0

T_{3,2} = 0

**Related Questions**

Linear Algebra - a)Let v be a fixed vector in R^3. Show that the transformation ...

Linear Algebra - (1) Define T:R->R be a linear transformation such that T(x,y...

Algebra - Determine if the relationship represented in the table is linear. If ...

Linear Alebra - Show that the transformation T:R^2->R^2 given T(x1,x2)=(3x1-...

Linear Algebra - Consider the linear transformation T: R^3->R^3 which acts by...

Algebra II - Determine if the following equation is linear. -7^2+y^2-y^2=3x+7 ...

Linear Algebra 2 - Let V and W be vector spaces over a field and let T:V->W ...

Linear Algebra - Suppose T: R^2->R^2 is a linear transformation with T(1,2)=(...

Math - Show that the transformation T:R^2->R^2 given T(x1,x2)=(3x1-5x2,x1+2x2...

Math - Let T: R^3 -> R^3 be a linear transformation whose matrix, with ...